Evaluation of degradation degree of dental ceramic/polymer composites for permanent fillings - Siejka-Kulczyk, J.; Lewandowska, M.; Kurzydłowski, K. J. (Polimery, 2022)
The aim of this study was to evaluate the degradation processes that take place in the dental hybrid composites intended for permanent fillings. The mixture of bis-GMA and TEGMA resins was used as the polymer matrix. Ceramic glass of various particle sizes as well as nanosilica were used as the composite fillers. The specimens were exposed to 0.1 M NaOH solution for 6, 24 or 168 h, and to water for 168 h. Degradation was evaluated by Scanning Electron Microscopy (SEM) microstructure observation and mechanical testing, such as flexural strength and microhardness. SEM investigations indicate that after the exposure to NaOH solution, the resin is partially dissolved and some filler particles have rinsed out. This deteriorates significantly the mechanical properties of ceramic/polymer composites.